Diversidade genética entre e dentro de variedades de cana-de-açúcar (Saccharum spp.) utilizando marcadores microssatélites - Maranho, Rone Charles (2012)
The purpose of this study was the molecular characterization of nine varieties of sugarcane grown in the northern region of Paraná, and used by one of the units producing sugar and ethanol, analyzing microsatellite loci. The analysis of polymorphism in microsatellite loci of these varieties should provide information on the variability present within each cultivar and genetic similarity and divergence between them. Forty primers were tested of which 17 were used for analysis of nine varieties of sugarcane, because they presented better definition. Among the 17 primers used only primers were monomorphic UGSM59 UGSM148 and being useful for the study of genetic uniformity of varieties. With the primers UGSM35, SEGMS240, SEGMS1069,SMC226CG, ESTB130, SMC1237FL, SMC165A, UGSM117, ESTB41, ESTB145, SMC1047HA, SMC2017FL, ESTC66, mSSCIR56 and ESTB50, were found a total of 70 alleles ranging from 2 to 6 alleles, a average of 4.12 alleles per locus. The analysis of polymorphism at 15 SSR loci of Saccharum spp showed that the loci Smc226CG, Smc1237FL, Smc1047HA, mSscir56 and EstB60 showed higher values for the estimates of observed heterozygosity, and in situ Smc1047HA found the largest number of alleles. The varieties RB72454, RB92579 and RB867515 showed the highest values of heterozygosity was observed. The calculated genetic diversity showed greater genetic identity among the varieties RB92579 and RB72454 with 86.31% similarity and the lowest similarity was found between the varieties and RB845210 RB835054. The SSR loci in varieties of sugarcane are promising markers for assessing the actual genetic diversity at the molecular level of varieties that have uniform agronomic characteristics, contradicting the assumption that there is genetic uniformity in commercial varieties of sugarcane.